Cryptic diversity of small‐sized species of Phalacroma (Dinophysales, Dinophyceae) from Denmark Strait (Eastern Arctic Greenland). Issue 3 (3rd February 2019) - Daugbjerg, Niels; Hansen, Stefan A.; Richardson, Katherine
SUMMARY: Phalacroma currently comprises 69 species of mostly marine heterotrophic dinophysoids. With a round cell body and short sulcal and cingular lists, Phalacroma spp. have a simple morphology compared to other dinophysoid genera. Therefore, species identification is not always a trivial matter. A few Arctic species have been described and, with the exception of Ph. rotundatum, they are not only infrequently recorded but also occur in low cell abundances. Here, we studied a Lugol fixed sample from Denmark Strait. From this sample 13 cells with a Phalacroma ‐like morphology were isolated under a stereo microscope, photo documented, and used for single‐cell PCR determination of nuclear‐encoded LSU rDNA sequences. The sequences fell in three groups defined by their ribotype. A single ribotype sequence representing each group was added to an alignment containing a diverse assemblage of dinophysoids and analyzed using Bayesian analysis and maximum likelihood. Based on comparative light microscopy one of the ribotypes (ribotype 1) was similar but not identical to Ph. ruudi and ribotype 2 could not be matched to a known species of Phalacroma . In the phylogeny both clustered with other species of Phalacroma including the type species. The morphology of ribotype 3 was similar but not identical to Ph. braarudii . In the phylogeny ribotype 3 clustered outside the core group of Phalacroma species. Hence, ribotype 3 was designated ' Phalacroma' sp. 3 and has to be described as a new genus pending additional data. This study has revealed the existence of cryptic species diversity within the Phalacroma morphotype boundary. Two additional Phalacroma species ( Ph. apicatum and Ph . cf. argus ) also clustered outside Phalacroma sensu stricto further emphasizing the presence of cryptic species within the genus. Future studies with a polyphasic approach are needed to better address the taxonomy of Phalacroma and Phalacroma ‐like dinophysoids.